Peculiarities of correction of sexual function in men presenting with diabetes mellitus - Roman Viktorovich Rozhivanov; Alexander Evgen'evich Lepetukhin; Sergey Anatol'evich Dubskiy; Dmitriy Gennad'evich Kurbatov (Сахарный диабет)
Diabetes mellitus (DM) is frequently associated with disturbances of the sexual function underlain by hypogonadism and neuropathy. These pathologicalconditions are successfully managed by androgens, alpha-lipoic acid, and phosphodiesterase type 5 inhibitors, besides compensation of carbohydratemetabolism. This paper reports results of evaluation of different methods for the treatment of erectile dysfunction in DM patients basedat Endocrinological Research Centre. Their combination ensured higher than 90% efficiency of therapy.